Cat Kid comic club - Pilkey, Dav, 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (New York : Graphix, 2020)
Join Li'l Petey, Flippy, and Molly as they introduce comic making to twenty-one funny, rambunctious, and talented frogs. Can the trio help the class unleash their own creativity?
3.7
3-6
GN520L
Keywords: Clubs -- Comic books, strips, etc. -- Juvenile fiction; Creative ability -- Comic books, strips, etc. -- Juvenile fiction; Cats -- Fiction; Frogs -- Fiction; Clubs -- Fiction; Drawing -- Fiction; Cartoons and comics; Humorous comics; Graphic novels; Comics (Graphic works)